From d8 to d1: Iron(0) and Iron(I) Complexes Complete the Series of Eight Fe Oxidation States within the TIMMNMes Ligand Framework - Gravogl, Lisa; Keilwerth, Martin; Körber, Eva; Heinemann, Frank Wilhelm; Meyer, Karsten (Inorganic Chemistry, 2024)
Reduction of the ferrous precursor [(TIMMNMes)Fe(Cl)]+ (1) (TIMMNMes = tris-[(3-mesitylimidazol-2-ylidene)methyl]amine) to the low-valent iron(0) complex [(TIMMNMes)Fe(CO)3] (2) is presented, where the tris(N-heterocyclic carbene) (NHC) ligand framework remains intact, yet the coordination mode changed from 3-fold to 2-fold coordination of the carbene arms. Further, the corresponding iron(I) complexes [(TIMMNMes)Fe(L)]+ (L = free site, η1-N2, CO, py) (3) are synthesized and fully characterized. Complexes 1-3 demonstrate the notable steric and electronic flexibility of the TIMMNMes ligand framework by variation of the Fe-N anchor and Fe-carbene distances and the variable size of the axial cavity occupation. This is further underpinned by the oxidation of 3-N2 in a reaction with benzophenone to yield the corresponding, charge-separated iron(II) radical complex [(TIMMNMes)Fe(OCPh2)]+ (4). We found rather surprising similarities in the reactivity behavior when going to low- or high-valent oxidation states of the central iron ion. This is demonstrated by the closely related reactivity of 3-N2, where H atom abstraction with TEMPO triggers the formation of the metallacycle [(TIMMNMes*)Fe(py)]+ (5), and the reactivity of the highly unstable Fe(VII) nitride complex [(TIMMNMes)Fe(N)(F)]3+ to give the metallacyclic Fe(V) imido complex [(TIMMNMesN)Fe(NMes)(MeCN)]3+ (6) upon warming. Thus, the employed tris(carbene) chelate is not only capable of stabilizing the superoxidized Fe(VI) and Fe(VII) nitrides but equally supports the iron center in its low oxidation states 0 and +1. Isolation and characterization of these zero- and monovalent iron complexes demonstrate the extraordinary capability of the tris(carbene) chelate TIMMN to support iron in eight different oxidation states within the very same ligand platform.
CRIS-Team Scopus Importer:2024-09-06